The Role Of Folk Traditions In Moral Education Young Generation - Abdimuratova Nilufar P, Abdimuratov Jalalatdin P (International Journal of Advanced Science and Technology, 2020)
The article is devoted to the formation of a spiritually rich, morally integral, harmoniously developed personality with an independent worldview and independent thinking, based on the invaluable heritage of our peoples traditions, customs and rites. Folk traditions developed on the basis of the life experience of many generations have educational potential and are an unwritten moral code for both the individual and society as a whole.